Koherensi pada Video Blog Berbahasa Jepang - Reny Wiyatasari; Mahardita Hideko (Universitas Diponegoro, 2022)
The aim of this research is to describe the elements of coherence in the discourse of Japanese video blog. The data of this research is taken from a video blog entitled ‘[Chōkai | Nihongo Kaiwa] Daigaku No Tomodachi to Hanasu Toki <Nihongo Joukyuushamuke>’ uploaded to YouTube on January 22, 2020. The data retrieval method used the referral method, using the tapping technique as its advanced technique. Furthermore, in the data analysis phase, using the ‘Agih’ method with the direct element sharing techniques. Then in presenting the data, using informal presentation methods.The results showed that there were 5 coherence data that showed interconnected discourse, seen from the use of cohesion markers. That way, the five datas can represent discourse coherence. <a href=